2013
DOI: 10.1182/blood-2012-08-449306
|View full text |Cite
|
Sign up to set email alerts
|

A role for miR-155 in enabling tumor-infiltrating innate immune cells to mount effective antitumor responses in mice

Abstract: Key Points miR-155 knockdown in myeloid cells accelerates spontaneous breast cancer development. miR-155 is required by TAMs for deploying antitumoral activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
96
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(99 citation statements)
references
References 50 publications
3
96
0
Order By: Relevance
“…Several miRNAs have been implicated in the regulation of macrophage activation and polarization 23,57-59 ; however, only a few have been studied in the context of cancer 9,[24][25][26]60 . Bioinformatics modelling of the transcriptional profiles of D −/− and D +/+ TAMs identified the Let-7-5p-family miRNAs as candidate negative regulators of M1 TAM activation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several miRNAs have been implicated in the regulation of macrophage activation and polarization 23,57-59 ; however, only a few have been studied in the context of cancer 9,[24][25][26]60 . Bioinformatics modelling of the transcriptional profiles of D −/− and D +/+ TAMs identified the Let-7-5p-family miRNAs as candidate negative regulators of M1 TAM activation.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have also begun to unravel the properties of individual miRNAs in TAMs. For example, miR-511-3p, miR-155-5p and miR-142-3p were all shown to limit M2-like macrophage activation in tumours 9,[24][25][26] . In this study, we genetically inactivated DICER in macrophages to analyse the effects of broadly disrupting miRNA activity on the immunoregulatory functions of TAMs.…”
mentioning
confidence: 97%
“…They also found that miR-155 reveals antitumoral effect by acting as an integral effector of immunosurveillance, thereby inhibiting the early stages of breast cancer development. 115 On the other hand, programmed cell-death protein 1 and programmed cell death 1 ligand 1 (PD-1/PD-L1) eliminate T-cell activation in various forms of cancer. 116 The prospective trials to evaluate the efficacy of antibodies to PD-1/PD-L1 are undergoing in patients with TNBC.…”
Section: Mirna In Triple-negative Breast Cancermentioning
confidence: 99%
“…miR-155 is one such microRNAs that is considered to play a critical role in promoting macrophage polarization to the M1 phenotype [22]. Similarly TAM's, which overexpress miR-155, have significantly decreased tumor cell survival, promote tumor cell apoptosis and inhibit tumor cell invasion [23]. Thus miR-based re-polarization of macrophages provides a novel strategy for macrophage mediated cancer therapy.…”
Section: Discussionmentioning
confidence: 98%